EFFECT OF MODERATE INTENSITY EXERCISE TRAINING ON PULMONARY FUNCTIONS IN YOUNG NORMAL AND OBESE ADULTS - AKHIL ANTONY.K,; A.CHRISTY,; D.SAMUEL SUNDAR DOSS,; K.REKHA, (International Journal of Pharma and Bio Sciences, 2015)
Obesity has become a major health issue in India. This study proposed to perform moderate intensity exercise training on pulmonary functions in young normal and obese adults. It was carried out among 60 subjects. The study group included 30 obese subjects and the control group included 30 normal weight subjects. There were 15 females and 15 males in each group. 15 minutes of exercise of moderate intensity was performed by subjects. Pulmonary Function Testing values were then taken. Obesity has a negative effect on pulmonary function test in young adult males, but not so in young adult females. There was a significant decrease in Pulmonary Function Testing values measured before exercise in obese young adult males and but not in obese young adult females. There was a significant increase in Pulmonary Function Testing values measured after exercise in both groups. Thereby study shows the need of exercise in improving the pulmonary function in both obese and non-obese young adults.